Penerapan green dentistry dalam praktik kedokteran gigi - Hapsari Andayani, Lia; Gani Soulisa, Abdul (Fakultas Kedokteran Gigi Universitas Trisakti, 2024)
Environmental breakdown and global warming have become two of the important issues today. One of the factors contributing to those issues is improper waste management. Medical waste from dental practices significantly contributes to pollution and accumulated waste, causing environmental degradation. The concept of Green Dentistry was introduced in 2007 as a solution to preserve natural resources and reduce waste. Green Dentistry is a multi-sectoral approach based on the 4R principles: Reduce, Reuse, Recycle, and Rethink. Reduce means reducing the consumption of resources as well as becoming more energy efficient. Reuse involves encouraging the prolonged use of an item to prevent substantial waste production. Recycle refers to reprocessing an item into a new product so that it can be useful again. Rethink means redeveloping mindset as a strategy to change, as well as promoting effective alteration. Practices aligned with the concept of Green Dentistry need to be implemented to achieve environmental sustainability. Ideas of forming an eco-friendly dental practice must be supported with knowledge and feasible solutions to overcome the barriers.